Download presentation

Presentation is loading. Please wait.

Published byPierce Whitehead Modified over 8 years ago

1
THE ELIMINATION METHOD Solving Systems of Three Linear Equations in Three Variables

2
Solutions of a system with 3 equations The solution to a system of three linear equations in three variables is an ordered triple. (x, y, z) The solution must be a solution of all 3 equations.

3
Is (–3, 2, 4) a solution of this system? 3x + 2y + 4z = 11 2x – y + 3z = 4 5x – 3y + 5z = –1 3(–3) + 2(2) + 4(4) = 11 2(–3) – 2 + 3(4) = 4 5(–3) – 3(2) + 5(4) = –1 Yes, it is a solution to the system because it is a solution to all 3 equations.

4
Use elimination to solve the following system of equations. x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6

5
Step 1 Rewrite the system as two smaller systems, each containing two of the three equations.

6
x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6 x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6

7
Step 2 Eliminate THE SAME variable in each of the two smaller systems. Any variable will work, but sometimes one may be a bit easier to eliminate. I choose x for this system.

8
(x – 3y + 6z = 21) 3x + 2y – 5z = –30 –3x + 9y – 18z = –63 3x + 2y – 5z = –30 11y – 23z = –93 (x – 3y + 6z = 21) 2x – 5y + 2z = –6 –2x + 6y – 12z = –42 2x – 5y + 2z = –6 y – 10z = –48 (–3) (–2)

9
Step 3 Write the resulting equations in two variables together as a system of equations. Solve the system for the two remaining variables.

10
11y – 23z = –93 y – 10z = –48 11y – 23z = –93 –11y + 110z = 528 87z = 435 z = 5 y – 10(5) = –48 y – 50 = –48 y = 2 (–11)

11
Step 4 Substitute the value of the variables from the system of two equations in one of the ORIGINAL equations with three variables.

12
x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6 I choose the first equation. x – 3(2) + 6(5) = 21 x – 6 + 30 = 21 x + 24 = 21 x = –3

13
Step 5 CHECK the solution in ALL 3 of the original equations. Write the solution as an ordered triple.

14
x – 3y + 6z = 21 3x + 2y – 5z = –30 2x – 5y + 2z = –6 –3 – 3(2) + 6(5) = 21 3(–3) + 2(2) – 5(5) = –30 2(–3) – 5(2) + 2(5) = –6 The solution is (–3, 2, 5).

15
It is very helpful to neatly organize your work on your paper in the following manner. (x, y, z)

16
Try this one. x – 6y – 2z = –8 –x + 5y + 3z = 2 3x – 2y – 4z = 18 (4, 3, –3)

17
Here’s another one to try. –5x + 3y + z = –15 10x + 2y + 8z = 18 15x + 5y + 7z = 9 (1, –4, 2)

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google